Dinamika Manajemen Madrasah Terpadu Dengan Sistem Pembelajaran Siang: Studi Kasus Kepemimpinan Di MTs Annur - Mochammad Nur Syawalludin Nugroho; Hartinah; Mohammad Masykur; Muhammad Rusdi Rasyid; Khatipah (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2026)
This study aims to analyze the implementation of Islamic education management and the leadership strategies of the madrasah principal in managing the daytime learning system under conditions of limited facilities and infrastructure at MTs Annur in Sorong City. This is a qualitative study using a case study design involving 19 informants, consisting of the madrasah principal, vice principal, teachers, administrative staff, and students selected through purposive sampling. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed interactively through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that management functions including planning, organizing, executing, and supervising are carried out adaptively and contextually in response to space constraints through the implementation of the daytime learning system. Furthermore, the madrasah principal’s leadership strategies, which are oriented toward exemplary conduct, service, and participation, contribute to fostering a work culture that is disciplined, communicative, and collaborative. The integration of management functions with the values of servant leadership has proven to support the effectiveness of learning as well as organizational sustainability. This study recommends strengthening adaptive leadership and developing a service-based management model in the administration of madrasahs facing resource constraints.